2021
DOI: 10.1186/s12957-020-02116-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a prognostic gene signature of colon cancer using integrated bioinformatics analysis

Abstract: Background Colon cancer is a worldwide leading cause of cancer-related mortality, and the prognosis of colon cancer is still needed to be improved. This study aimed to construct a prognostic model for predicting the prognosis of colon cancer. Methods The gene expression profile data of colon cancer were obtained from the TCGA, GSE44861, and GSE44076 datasets. The WGCNA module genes and common differentially expressed genes (DEGs) were used to scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 72 publications
0
15
0
Order By: Relevance
“…WDR78 is essential for ciliary beating and axonemal dyneins. Studies showed that WDR78 has been enrolled in the molecular signatures for predicting the prognosis of CRCpts ( 63 , 64 ). In further studies, we will explore the specific roles and mechanisms of the five genes in 5-Fu resistance in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…WDR78 is essential for ciliary beating and axonemal dyneins. Studies showed that WDR78 has been enrolled in the molecular signatures for predicting the prognosis of CRCpts ( 63 , 64 ). In further studies, we will explore the specific roles and mechanisms of the five genes in 5-Fu resistance in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there is a reported prognostic signature of 6-lncRNA and 12-gene for CRC [ 37 , 38 ]. Like the data of the TCGA database, we also found LINC01224 abundance was elevated in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Least Absolute Shrinkage and Selection Operator (LASSO) is a commonly used regularization in many regression analysis methods for variable selection and shrinkage in Cox's proportional hazards model [28]. Lasso penalized Cox regression analysis have been widely used to construct gene expression based signatures in various cancers [29][30][31]. In our study, the FRlncRNAs were used as input of Lasso Cox regression to construct a FRlncRNA signature.…”
Section: Data Collectionmentioning
confidence: 99%